'Frere's War'? A reconstruction of the geopolitics of the Anglo-Zulu War of 1879 - Dominy, G. (Southern African Humanities, 2021)
The Anglo-Zulu War continues to attract considerable attention from historians, but the motives and the timetable for the British invasion of Zululand in 1879 remain comparatively under-researched. In this paper the debate surrounding the 'causes' of the Anglo-Zulu War within the context of the expansion of British hegemony in southern Africa following the discovery of diamonds is discussed. Special attention is paid to C. de B. Webb's views on Frere's attempts to mislead the British government as to his 'forward policy' regarding Zululand. Frere's handling of the award of the Boundary Commission is discussed and a revision of Webb's findings is offered. The paper concludes by situating Frere's policy on the subjugation of the Zulu kingdom within the context of his subcontinental policy with particular reference to the Transvaal. To cite this paper: Dominy, G. 1993. 'Frere's War'? A reconstruction of the geopolitics of the Anglo-Zulu War of 1879. Natal Museum Journal of Humanities 5: 189-206.